Research on mathematics anxiety in primary school: bibliometric analysis and evaluation of trends - Hilal Uğraş (Frontiers in Psychology)
IntroductionMathematics anxiety is a persistent barrier to effective learning, particularly in primary education. Understanding how this phenomenon has evolved in academic literature can help guide educational strategies and psychological interventions. This study aims to explore trends and key themes in research on mathematics anxiety in primary school students over a 45-year period.MethodsA bibliometric analysis was conducted using data retrieved from the Web of Science (WOS) and Scopus databases. The study included 404 articles published between 1979 and 2024. The analysis was performed using the RStudio environment with the Biblioshiny package. The research process involved study design, data collection, statistical analysis, data visualization, and interpretation.ResultsFindings indicate that research on mathematics anxiety in primary school remained limited for several decades but has gained substantial attention in recent years. The field demonstrates an interdisciplinary nature, with contributions from both psychological and educational research domains. Key authors, journals, institutions, and countries contributing to the field were identified, highlighting global academic interest.DiscussionThe results suggest a growing scholarly focus on the effects of mathematics anxiety, including how cognitive, emotional, and social factors contribute to its development and management. The interdisciplinary expansion reflects a deeper exploration into individual differences and their role in mathematics learning. These findings underscore the need for continued integrated research in addressing mathematics anxiety at early educational stages.